2018
DOI: 10.1111/ecc.12872
|View full text |Cite
|
Sign up to set email alerts
|

Guilt among husband caregivers of Chinese women with breast cancer: The roles of male gender-role norm, caregiving burden and coping processes

Abstract: Caregiver guilt (i.e., feeling of inadequacy in providing care to patients) is commonly experienced and studied among husbands of breast cancer survivors in Western countries. However, little is known about the psychosocial correlates of caregiver guilt in their Chinese counterparts. A total of 176 husbands of Chinese breast cancer survivors completed a cross-sectional survey in Weifang, Shandong province, China. As expected, hierarchical regression results showed that higher caregiving burden was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 74 publications
2
35
0
4
Order By: Relevance
“…Participants described that caregiving was entrenched in the Ghanaian cultural values; hence, the decision to care was viewed as an automatic obligation. This finding supports earlier evidence that describes caregiving as a communal family activity that is shaped by cultural norms [19]. Further, from our study, there were gender prescriptions in which females, specifically mothers and older daughters, were supposed to assume the caring role.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Participants described that caregiving was entrenched in the Ghanaian cultural values; hence, the decision to care was viewed as an automatic obligation. This finding supports earlier evidence that describes caregiving as a communal family activity that is shaped by cultural norms [19]. Further, from our study, there were gender prescriptions in which females, specifically mothers and older daughters, were supposed to assume the caring role.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, our findings indicated that there were marital obligations in which male spouses were the main primary caregivers. This evidence was further confirmed in Yeung et al's [19] quantitative study of male spouses who cited that marital obligation may influence the decision to accept the role of caregiving for women living with advanced breast cancer. Also, our finding that caregiving was based on reciprocity supports previous research which showed that caregiving can be viewed as a form of repaying of good deeds formerly obtained from patients [48].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Following the full-text screening, 107 were excluded because they did not meet the inclusion criteria as detailed in the PRISMA flow diagram. At the end of the screening procedure, 19 peer-reviewed citations remained for final inclusion in the review [3,4,6,10,15,[17][18][19][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The majority of the included studies (n = 15) used quantitative approaches [3,10,15,18,19,[23][24][25][26][27][28][30][31][32][33] and the remaining (n = 4) were qualitative studies [4,6,17,29]. Studies were conducted in the following countries: Nigeria (n = 2), Malaysia (n = 3), Ghana (n = 1), China (n = 3), Iran (n = 6), Turkey (n = 1), Mexico (n = 1), Indonesia (n = 1), and India (n = 1).…”
Section: Methodsological Characteristics Of Included Studiesmentioning
confidence: 99%